Implementation of the Wasoya Book in Improving the Noble Morals of Second Grade Wustho Putra Students at the Tri Bhakti At Taqwa Diniah Madrasah - Permana, Luna; Aziz, Ikhwan; Azizah, Isnaini Nur (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to examine the implementation of the Wasoya Book in improving the noble morals of second-grade Wustho Putra students at Madrasah Diniah Tri Bhakti At-Taqwa, East Lampung. The Wasoya Book is one of the classic books that contains advice and Islamic moral values ​​that are relevant in fostering the character of students in the Islamic boarding school environment. This study uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation. Informants in this study include the Wasoya Book teacher, the head of the madrasah, and second-grade Wustho Putra students. The results of the study indicate that the implementation of the Wasoya Book is carried out through interactive lecture methods, discussions, mudzakarah, and giving reflective assignments to encourage the appreciation and practice of moral values. The main values ​​emphasized include honesty, responsibility, patience, humility, and love of knowledge. Learning evaluation is carried out through observation of attitudes, oral and written tests, and practical assignments that reflect the understanding and practice of morals.This study found significant changes in the behavior of students after participating in the Wasoya Book learning, including increased discipline, politeness in speaking and acting, and a sense of caring for others. However, the process of internalizing morals also faces challenges, such as the diverse background of students' understanding, lack of support from the family environment, and the negative influence of social media. Overall, the results of this study indicate that the Wasoya Book has an important role in instilling noble moral values ​​and is worthy of continued development in Islamic boarding school education.